Urban Heat Island Effect Analysis of Kathmandu Metropolitan City in Nepal - Poudel, Sudipta; Dhital, Ishwor Pd. (Journal of Land Management and Geomatics Education, 2025)
Rapid urbanization and anthropogenic activities have significantly altered the thermal environment of Kathmandu Metropolitan City, creating a pronounced Urban Heat Island (UHI) effects that threaten urban livability and climate resilience. This study examines the spatial-temporal evolution of UHI patterns in Kathmandu over a decade (2015-2024) using multi-temporal satellite remote sensing data. The research integrates Normalized Difference Vegetation Index (NDVI), Normalized Difference Built-up Index (NDBI), and Land Surface Temperature (LST) derived from Landsat 8/9 thermal infrared bands and Sentinel-2 multispectral imagery to quantify land cover transformations and their relationship with urban thermal patterns. Results indicated drastic urban expansion accompanied by severe vegetation loss, leading to intensified heat island effects across the rapidly developing areas. Maximum LST increased substantially from 26.28° C in 2015 to 35.85° C in 2023, representing a 9.57° C increase over eight years. The urban-rural temperature gradient intensified from 5.2° C to 8.7° C, while built-up areas expanded by 15.2% with dense vegetation declining by 8.7% of the total area. Strong correlations were observed between NDBI and LST (r = 0.78), NDVI and LST (r = -0.72, confirming the cooling effect of vegetation and heating effect of built surfaces. The eastern and northern sectors of the city experienced the most pronounced thermal intensification, with newly developed areas showing temperature increases of 7.1-8.2° C. Urban heat islands are increasingly problematic in an era of rapid urbanization and climate change.